Review of Collaboration between NMWCP and REDD+ in Supporting Sustainable Forest Management in Papua - Gun Mardiatmoko (Institut Pertanian Bogor (IPB University), 2013)
Various programs on sustainable forest-soil-water management have been developed and occasionally conducted by the Indonesian Ministry of Forestry, Ministry of Agriculture, and Ministry of Public Works under various programs. Unfortunately, the achievement of such programs were not satisfactorily. Currently, there exist 2 inter-sectoral initiatives called the National Movement for Water Conservation Partnership (NMWCP) that focused on water conservation and Reducing Emission from Deforestation and Forest Degradation (REDD+) that focused on emission reduction of greenhouse gasses through reducing deforestation and forest and land degradation. Both programs could be closely linked to carbon trade mechanism as a potential of gaining international financial supports. In principal and function-wise, the 2 programs were not distinct, particularly with regard to managing deforestation, forest degradation, forest-land-water conservation, and community empowerment/stakeholders. In principle, water conservation is inherent with forest function. In the other side, Papua is a vast region dominated by mountainous area comprises of many watersheds. In this regards, the need of having an Integrated Watershed Management (IWM) is inevitable. Therefore, collaboration between the 2 inter-sectoral programs could be the best solution for Papua. Through collaboration scheme, it would be possible to involve wider stakeholders and have more potential of generating international financial supports to carry out a more effective and efficient management of forest, land, and water.